Controllable embedding of size‐selected copper nanoparticles into polymer films. Issue 5 (10th January 2020) - Bonde, Hans Christian; Fojan, Peter; Popok, Vladimir N.
Abstract: The ability to control the extent of metal nanoparticle (NP) embedding into polymer films has attracted attention for applications in quite a few research branches. In this study, the behavior of size‐selected copper NPs produced by the gas aggregation method and deposited on poly(methyl methacrylate) and polystyrene films is studied under thermal annealing above and below the glass transition temperature. Several important tendencies of the embedding dynamics in terms of dependence on NP size, annealing temperature, and time, as well as the type of polymer, are found and analyzed. Physical models explaining particle behavior and allowing the elaboration of practical recommendations on the controllable embedding of metal NPs into polymer films are suggested. Abstract : Polymer films with metal nanoparticles are of interest for applications in electronics, optics, sensing as well as in biological and medical branches. We present an approach for controlling the extent of metal nanoparticle embedding into polymer films and the results of a systematic study on the dynamics of this process as a function of particle size, annealing temperature, and type of polymer.